Accidental aspiration of denture cleanser tablets caused severe mucosal edema in upper airway. (7th March 2016) - Ochi, Nobuaki; Yamane, Hiromichi; Honda, Yoshihiro; Takigawa, Nagio
Abstract: A 78‐year‐old man accidentally swallowed denture cleanser tablets (Polident ® ). Although he immediately spat them out, he felt difficulty in breathing. Observation using a fiber optic bronchoscope revealed a constricted glottis with edema and redness. The instillation of 1% xylocaine with epinephrine to the epiglottis and larynx reduced the edema and enabled the bronchoscope to pass the glottis. Red and edematous mucosa of the trachea and major bronchus were also observed. We should be aware that accidental aspiration of denture cleansers may cause laryngeal edema.